Pediatric pulmonary year in review 2021: Sleep medicine. Issue 10 (8th July 2022) - Okorie, Caroline U. A.; Afolabi‐Brown, Olufunke; Tapia, Ignacio E.
Abstract: Pediatric pulmonology publishes original research, review articles, and case reports on a wide variety of pediatric respiratory disorders. In this article, we summarized the past year's publications in sleep medicine and reviewed selected literature from other journals in this field. We focused on original research articles exploring aspects of sleep‐disordered breathing in patients with underlying conditions such as cystic fibrosis, asthma, and sickle cell disease. We also explored sleep‐disordered breathing risk factors, monitoring, diagnosis, and treatment; and included recent recommendations for drug‐induced sleep endoscopy and ways to monitor and improve PAP adherence remotely.